Model construction and validation of airflow velocity attenuation through pear tree canopies - Zhang, Fubin; Sun, Hao; Qiu, Wei; Lv, Xiaolan; Chen, Yunfu; Zhao, Guozhu (Frontiers in Plant Science, 2022)
To investigate the airflow velocity attenuation inside pear tree canopies and the factors that influence its effect on air-assisted spraying, the relationship between the resistance of the canopies to airflow and airflow velocity inside the canopies was determined. At the same time, the theoretical model of airflow velocity attenuation in the canopy was constructed, in which the velocity attenuation factor k and the incoming velocity were the model input values, and the airflow velocity in the canopy was the model output value. Then, experimental verification of the theoretical model was completed. The determination test of airflow velocity inside canopies with three leaf area densities revealed that the error range between the established theoretical model and the experimental airflow velocity inside the pear tree canopy was 0.11–1.25 m/s, and the mean size of the model accuracy was 83.4% under various working conditions. The results revealed that the region from a depth of 0 m to 0.3 m inside the canopy was the rapid attenuation area of the airflow and that from 0.3 m to 0.9 m was the low attenuation area. Furthermore, they revealed that high-speed airflow could strongly disturb the outer branches and leaves, greatly changing the windward area of the canopy blades and thus affecting the accuracy of the model. By introducing a dynamic parameter of the canopy leaf windward area for model correction, the R2 of the model was above 0.9. Finally, validation of the model was performed in an air-assisted spraying operation in an orchard. This study can provide a theoretical basis for the regulation of airflow parameters of air-assisted spraying of pear trees.